Analisis Pengembangan Budaya Literasi dalam Meningkatkan Minat Membaca Siswa Kelas VI di SD Negeri Tobitalerek Kecamatan Nubatukan - Fajrina Asrianty; Jusmaniar Nonci; Rahma Ashari Hamzah (STKIP Andi Matappa Pangkep, 2022)
Study Aims to determine the development of a literacy culture in increasing the reading interest of grade VI students, the factors causing the obstacles to developing a literacy culture in increasing the reading interest of grade VI students, and the teacher's solution in overcoming the obstacles to developing a literacy culture for grade VI students. The results of the study are the development of a literacy culture to increase interest in reading for grade VI students is carried out by a process of habituation, development, and learning, the factors causing obstacles to the development of a literacy culture are reading habits that have not been instilled early on, access to educational facilities that have not been evenly distributed, increased use of technology , reading activities have not become a priority for students' main activities, inadequate libraries, and reading habits that are not made a habit at home, the solution to overcome the obstacles to developing a literacy culture is to instill awareness in students and parents that reading is very important, provide a variety of books that appropriate, arranging the school library to keep it clean and tidy, giving prizes to students who diligently read a book, and doing activities responding to enrichment books.